Zasady i warunki przesłuchania w trybie art. 308 § 2 k.p.k. - Komar-Zabłocka, Magdalena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Artykuł poświęcony jest czynności przesłuchania w ramach prowadzenia dochodzenia w niezbędnym zakresie. Dokonano analizy przesłanek przesłuchania osoby podejrzanej w charakterze podejrzanego, procedury przesłuchania w tym trybie oraz terminów prowadzenia czynności w niezbędnym zakresie. Dla uzupełnienia tej problematyki nie sposób byłoby pominąć omówienia prawnych podstaw prowadzenia czynności faktycznego wszczęcia postępowania.

The article discusses the interrogation activities as part of conducting the investigation to the necessary extent. The author analyzes the premises of a suspect person’s (the person against whom the decision on the submission of charges has not been issued yet) interrogation as a suspect, the procedure of interrogation in this procedure and the time limits for carrying out activities to the necessary extent. To complement this issue, the article discusses the legal basis for conducting the actual act of initializing criminal proceedings.
Keywords: dochodzenia; podejrzany; przesłuchanie; zarzuty; investigation; suspect; hearing; charges